2006
DOI: 10.1073/pnas.0608777103
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila flies in “Evolution Canyon” as a model for incipient sympatric speciation

Abstract: The genetic basis of population divergence leading to adaptive radiation and speciation is a major unresolved problem of evolutionary biology. Molecular elucidation of ''speciation genes'' advanced recently, yet it remains without clear identification of the gene complexes participating in reproductive isolation between natural populations, particularly, in sympatry. Genetic divergence was discovered between Drosophila melanogaster populations inhabiting ecologically contrasting, opposite slopes in ''Evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 68 publications
1
63
1
Order By: Relevance
“…Nevertheless, significant interslope D. melanogaster populations' divergence was established in EC I involving habitat choice, mate choice, reproductive activity, courtship song patterns, significant positive assortative mating, 144 thermal and drought tolerances, adaptive genes, and mobile elements as well as various aspects of induced changes in viability and longevity caused by short-term and lifetime high temperature treatments. 33,142,143 Remarkably, parallel patterns of stress tolerance, habitat choice, and mate choice were also demonstrated in Drosophila simulans at EC although on a smaller scale. The combined prezygotic and postzygotic evidence suggest that D. melanogaster at EC incipiently speciates sympatrically as was shown also in Bacillus simplex, wild barley Hordeum spontaneum, and spiny mice Acomys cahirinus.…”
Section: Prezygotic Sexual and Reproductive Behavior Isolation And Imentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, significant interslope D. melanogaster populations' divergence was established in EC I involving habitat choice, mate choice, reproductive activity, courtship song patterns, significant positive assortative mating, 144 thermal and drought tolerances, adaptive genes, and mobile elements as well as various aspects of induced changes in viability and longevity caused by short-term and lifetime high temperature treatments. 33,142,143 Remarkably, parallel patterns of stress tolerance, habitat choice, and mate choice were also demonstrated in Drosophila simulans at EC although on a smaller scale. The combined prezygotic and postzygotic evidence suggest that D. melanogaster at EC incipiently speciates sympatrically as was shown also in Bacillus simplex, wild barley Hordeum spontaneum, and spiny mice Acomys cahirinus.…”
Section: Prezygotic Sexual and Reproductive Behavior Isolation And Imentioning
confidence: 95%
“…This complex involved either adaptation traits (tolerance to high temperature, different viability, and longevity pattern) or behavioral differentiation manifested in habitat choice 146 and non-random mating. 33,142,143 This remarkable differentiation has evolved despite a very small interslope distance (200 meters on average, while Drosophila can fly 10 km or more!). Our hypothesis is that strong interslope microclimatic divergence accentuated sexual isolation as a by-product of slopespecific adaptations initiating incipient sympatric speciation following the Darwin-MullerMayr model.…”
Section: Prezygotic Sexual and Reproductive Behavior Isolation And Imentioning
confidence: 99%
“…Surprisingly, and in contrast to theoretical expectations, the examples of unequivocal SS in animals are scanty (1), although quite abundant in polyploid plants. Recently, a flow of novel SS cases, proven or hypothesized, have been proposed (2,7,(29)(30)(31)(32)(33)(34). The EC case clearly demonstrates how incipient sympatric climatic ecological speciation (35) occurs across life from bacteria through fungi, plants (wild barley), insects (Drosophila and the beetle Oryzaephilus surinamensis), to mammals [spiny mice Acomys described here and in (7)].…”
Section: Discussionmentioning
confidence: 99%
“…In all of these distant taxa, strong interslope natural microclimatic selection overrides the homogenizing effects of the ongoing restricted gene flow (4, 7). Remarkably, the flying Drosophila migrates between the slopes (6) but displays multiple slope-specific adaptive complexes to the abutting slope's stresses (30). It speciates sympatrically based on mate and habitat choices, positive assortative mating (39) reinforced by slope-specific courtship songs (40).…”
Section: Discussionmentioning
confidence: 99%
“…This species has been one of the major model organisms in the EC I research program. In a series of studies reviewed in Korol et al (74,75), Nevo et al (49), and Rashkovetsky et al (76), we have shown multiple adaptive interslope divergence and incipient sympatric ecological speciation (all articles listed in Nevo's list of EC, found at http://evolution.haifa.ac.il). By means of the capture-mark-release-recapture method, we studied the migration pattern from AS to ES and vice versa (32).…”
Section: Signals Of Global Warming At Ec I: Preliminary Realized Predmentioning
confidence: 99%